Analisis Kompetensi Pedagogik Guru Biologi SMA Di Kabupaten Aceh Tamiang - Mardiana, Mardiana; Harahap, Fauziyah; Syarifuddin, Syarifuddin (Jurnal Pendidikan Biologi, 2017)
The objective of this study is to find out how biology teacher paedogogical competency of senior high schools in Aceh Tamiang regency. This study involved all of the high schools in Aceh TamiangÂ regency. The population in this studyconsist of 54 biology teachers in Aceh Tamiang regency. The sample of this study consist of 34 biology teachers. In this study, observation in high school class was done by using the instrument called Penilaian Kinerja Guru (PK Guru) which has been modified by researcher. This sutdy uses descriptif quantitatif research methode by using numbering and then the number is explained by using the sentences. The result of this study shows the paedogogical competency of biology teacher is Â verygood including some aspect : 1)recognize the studentâs characteristic isÂ very good (80,40%), 2) having the ability the theory of teaching learning process and technique is very good (78,36%) 3). curiculum developing Â is very good (77,33%) 4) teaching learning process Â is very goodÂ (80,31% ), 5)knowing and developing student ability is very good (80,02%),6) communicating with the studentâs is very good (83,09% )7) assessment and evaluation is very good(80,15%). There are some obstacles that biology teachers should face regarding teaching, teachers have not been able to developing syllabus from BSNP based on students characteristics and condition of local region. In addition the result of study on curiculum developing to design worksheets and module obtained are very low 63%, then in the aspects having the ability the theory of teaching learning process and technique the ability of teachers to invite students learn to recognize enviroment and provide oppurtunities for students to make observation and experiments were also obtainedÂ a low value 74%.